2021
DOI: 10.3390/nu13030811
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Escherichia coli Ameliorates Antibiotic-Associated Anxiety Responses in Mice

Abstract: Despite the beneficial actions of antibiotics against bacterial infections, the use of antibiotics is a crucial etiological factor influencing microbial dysbiosis-associated adverse outcomes in human health. Based on the assumption that gut microbial dysbiosis can provoke behavioral or psychological disorders, the present study evaluated anxiety-linked behavioral changes in a mouse model of streptomycin-induced dysbiosis. Measuring anxiety-like behavior using the light–dark box and elevated plus maze tests ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Thus, we aimed to mimic A. muciniphila overproliferation in C57BL/6 mice using vancomycin, as it was previously shown to elevate Akkermansia 41 . At the same time, this antibiotic is known for occasional strong outbreaks of Escherichia coli proliferation, which might also affect behavior [42][43][44] . We have shown previously that E. coli found in our in-house colony of C57BL/6 is particularly sensitive to rifampicin 45 , so we treated C57BL/6 mice with a combination of vancomycin and rifampicin (VR).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we aimed to mimic A. muciniphila overproliferation in C57BL/6 mice using vancomycin, as it was previously shown to elevate Akkermansia 41 . At the same time, this antibiotic is known for occasional strong outbreaks of Escherichia coli proliferation, which might also affect behavior [42][43][44] . We have shown previously that E. coli found in our in-house colony of C57BL/6 is particularly sensitive to rifampicin 45 , so we treated C57BL/6 mice with a combination of vancomycin and rifampicin (VR).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we aimed to mimic A. muciniphila overproliferation in C57BL/6 mice using vancomycin, as it was previously shown to elevate Akkermansia (Ray et al, 2020). At the same time, this antibiotic is known for occasional strong outbreaks of Escherichia coli proliferation, which might also affect behavior (Jang et al, 2018; Kim et al, 2020; Park et al, 2021). We have shown previously that E. coli found in our in-house colony of C57BL/6 is particularly sensitive to rifampicin (Borisova et al, 2020a), so we treated C57BL/6 mice with a combination of vancomycin and rifampicin (VR).…”
Section: Resultsmentioning
confidence: 99%
“…Although the authors of that report also did not take into account differences between animals of both sexes, they observed that streptomycin treatment significantly increased anxiety in mice in the light-dark box test and in the elevated plus-maze test. Again, they also suggested a dysbiosis of the gut microbiome as a potential cause of the observed disturbances ( 27 ). The long-term effects of the low-dose penicillin intake by pregnant mice on these animals and their offspring shortly after the birth were also studied ( 28 ).…”
Section: Discussionmentioning
confidence: 99%